10,000 job opportunities in UMP Career Fair - Nur Laila, Afandi (2018)
Kuantan, 21st April – More than 40 companies participated in Career Fair organized by Career Placement & Development Centre (CPDC). With the theme ‘University to Industry’, this career fair offers more than 10,000 job opportunities to the visitors.